Stateless And Abandoned: The Foundling In Malaysia - Chen, Vivien J.H. (Journal of Malaysian and Comparative Law, 2019)
Citizenship denotes allegiance as well as a sense of belonging to a country. In return for such allegiance, certain benefits are conferred exclusively on citizens of the country. A person who is not a citizen of any country is a stateless person. Having no citizenship in a country, she is a perpetual alien, even in her country of origin and domicile. A stateless person has been likened to a vessel on the open sea not sailing under the flag of a state, or a bird that flies alone.